Metaphysical Speculations and Linguistic Pyramids In the Work of a Raja Rao: Exploring Metaphysical and Linguistic Speculations in Raja Rao's Works (Journal of Advances and Scholarly Researches in Allied Education, 2011)
Thehouse of fiction that Raja has built is thus founded on the metaphysical andlinguistic speculations of the Indians. As Raja's editor at Oxford UniversityPress, I saw The Policeman and the Rosethrough the press, and it was published in 1978.